Японська релігійна свідомість - Тонґуу Масару (Народна творчість та етнографія, 2009)
The system of religious beliefs of the Japanese in their historical development is examined in the article. It is marked that one of the main lines of the Japanese religiousness is an aspiration to the real confirmation of beliefs and benefits from them in this life. Determining the Japanese religiousness as a "difficult polytheism”, the author examines the role of the linear and cyclic way of thinking in the structure of religious consciousness, the mechanisms of its internal inheritance and the cultural borrowing from other cultures.